3D printing for energy applications - Tarancón, Albert; Esposito, Vincenzo (Wiley-American Ceramic Society, 2021)
"During the last three decades of intensive research on 3D printing, the focus of the development has been put on structural simple parts rather than on complex objects based on multiple functional materials. However, in the last years, the use of 3D printing for fabricating complex devices has become an emerging and promising topic, especially in the energy sector. This book covers aspects related to additive manufacturing of functional materials with applicability in the energy sector. The book comprehensively reviews both the technology itself (printable materials and 3D printing strategies) and its specific use in energy devices or systems. Split into three sections the book cover the 3D printing of functional materials; 3D printing of energy devices; and printing challenges for production of complex objects."--